Gastric Ulcer Healing Property of Bryophyllum pinnatum Leaf Extract in Chronic Model In Vivo and Gastroprotective Activity of Its Major Flavonoid - De Araújo, Edilane Rodrigues Dantas; Guerra, Gerlane Coelho Bernardo; Andrade, Anderson Wilbur Lopes; Fernandes, Júlia Morais; Da Silva, Valéria Costa; De Aragão Tavares, Emanuella; De Araújo, Aurigena Antunes; de Araújo Júnior, Raimundo Fernandes; Zucolotto, Silvana Maria (Frontiers in Pharmacology, 2021)
Gastric ulcer is a common disease that is able to develop complications such as hemorrhages and perforations when not properly treated. Extended use of drugs in treatment this pathology can provoke many adverse effects. Therefore, finding medicinal plants with gastroprotective and mucosal healing properties has gained increasing interest. Bryophyllum pinnatum (Crassulaceae), popularly known in Brazil as “saião” or “coirama”, has been used to treat inflammatory disorders. It is rich in flavonoids and quercetin 3-O-α-L-arabinopyranosyl-(12)-O-α-L-rhamnopyranoside-Bp1 is its major compound. In this study we had the aim to investigate ulcer healing properties of B. pinnatum against an acetic acid-induced chronic ulcer model and the gastroprotective activity of the Bp1 against gastric lesions induced by ethanol and indomethacin. Ultra-fast liquid chromatography was used to quantify the main compounds (mg/g of the extract) quercetin 3-O-α-L-arabinopyranosyl-(12)-O-α-L-rhamnopyranoside (33.12 ± 0.056), kaempferol 3-O-α-L-arabinopyranosyl-(12)-O-α-L-rhamnopyranoside (3.98 ± 0.049) and kaempferol 3-O-α-L-rhamnopyranoside (4.26 ± 0.022) and showed good linearity, specificity, selectivity, precision, robustness and accuracy. In vivo studies show that treatment with the extract at 250 and 500 mg/kg stimulated the healing process in the gastric mucosa with a significant ulceration index reduction, followed by improvement in the antioxidant defense system (increased glutathione levels, decreased superoxide dismutase upregulation and malondialdehyde levels). Moreover, the extract decreased interleukin-1β and tumor necrosis factor-a levels and myeloperoxidase activity, increased interleukin 10 levels, showed a cytoprotective effect in histological analyzes and also downregulated the expression of COX-2 and NF-κB (p65). The pre-treatment with Bp1 at dose of 5 mg/kg reduced the gastric lesions in ethanol and indomethacin models increased glutathione and decreased malondialdehyde levels. In addition, the pre-treatment was able to decrease myeloperoxidase activity, interleukin-1β and tumor necrosis factor-α levels, while also showing a cytoprotective effect in histological analyzes. Our study suggests that treatment with B. pinnatum extract showed a higher inhibition percentage when compared to pre-treatment with the Bp1. This might in turn suggest that Bp1 has gastroprotective activity, but other compounds can act synergistically, potentiating its effect. We conclude that B. pinnatum leaf extract could be a new source of raw material rich in phenolic compounds to be applied in food or medicine.